WOMEN'S REBELLION AGAINST POVERTY - Widyastuti, Thera (International Review of Humanities Studies, 2019)
Women's lives are generally in the domestic, where women do to raising children, taking care of their families, and husbands. Women are under the rule of men who always dominate their lives. Male domination applies among patriarchal. Many women are unable to resist this situation and surrender to accepting their situation. Novel Gadis Pesisir written by Ninuk Y Kusmiana in 2014 raised the story of women's lives and their problems. It tell the lives of fishermen on the island of Irian in 1970. They live poorly, and are very dependent on nature and the sea to feed them. The main character in this novel is Halijah, a young girl who lives as a poor fisherman child. She must work hard to help her parents do homework. She wants to rebel against the poor life she lived during her life. The problem in this article is the way of women motivate themselves to be better positioned in fishermen village on the island of Irian. While the purpose of this research is to find out the position of women among fishermen village. The research method used in this article is descriptive analysis and it uses literature study as the technique to collect the data. Gender role theory, symbolic capital, and sociology of literature are used to examine the existing problems, besides the theory of character in this novel. The description of existing data is done so that this article can run as expected. The findings data are described in such a way that they are analyzed.